Antibacterial Therapy and Prevention of Infectious Endocarditis in Modern Conditions - B. S. Belov; G. M. Tarasova; N. V. Muravyeva (Антибиотики и Химиотерапия)
The problem of infectious endocarditis (IE) still retains its importance due to high mortality rates and the development of severe complications. Modern IE is a polyethological disease, the occurrence and development of which can be caused by pathogens that make up an extremely extensive list, which is updated almost annually. At the same time, serious obstacles standing in the way of eﬀective antimicrobial therapy are both the increasing resistance of IE pathogens to antibiotics and the increasing etiological role of infectious agents that were previously very rare. This article presents the basic principles of treatment and prevention of IE, taking into account the latest recommendations of the experts of the European Society of Cardiology in 2023.